Labeling of Disease-Modifying Therapies for Neurodegenerative Disorders - Morant, Anne Vinther; Jagalski, Vivien; Vestergaard, Henrik Tang (Frontiers in Medicine, 2019)
Neurodegenerative disorders are characterized by progressive degeneration of nerve cells resulting in functional decline of cognition and/or movement. As the prevalence of many of these disorders increases with the aging global population, there is an urgent need for disease-modifying drugs that will halt or slow the progression of these devastating diseases. A summary of the scientific information needed to guide the safe and effective use of a drug is provided in the product label, in which the indication section should clearly state the treatment concept, i.e., distinguish between e.g. symptomatic, preventive and curative treatments. However, a review of the United States (US) and European Union (EU) product labels for disease-modifying multiple sclerosis (MS) drugs reveals that the indications are not aligned with the regulatory guidance on labeling. Indication claims such as ‘delay of accumulation of disability’ and ‘slowing of disease progression’ were previously accepted by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA); however, all recently approved MS drugs include no such specification of the treatment concept in the label indication sections despite similar clinical data packages supporting the approvals. Coincidently, the FDA and EMA therapeutic guidelines pertaining to development of drugs for treatment of neurodegenerative disorders have changed from providing recommendations for specific disease modification label claims to a more general focus on the clinical development approach. Our analysis of MS drug labels could imply that the FDA and EMA may be unlikely to accept disease modification-related indication claims for drugs to treat neurodegenerative disorders in general. We envision that a potential disease-modifying effect is more likely to be inferred from the label descriptions of the mechanism of action, clinical efficacy data and trial design, and target patient population. This poses a challenge for communication of the clinical benefit in a language that can be easily understood by patients and prescribers.